Navigating the ChatGPT Theological Terrain: Considerations for Graduate Theology Students - Mahlon Nyongesa Juma (Pan-African Journal of Education and Social Sciences)
With discussions across disciplines, AI technologies are here to stay. For both professors and students, academic debates raise ethical and moral questions. This study attempts to address the latter issue through these research questions: Can graduate theology scholars use ChatGPT for their publications? What are the advantages and drawbacks of using ChatGPT in scholarly publications for graduate Theology students? What are the implications for graduate Theology students? What guidelines should be followed when using ChatGPT? The literature shows that professors are already worried about potential scholastic perversions resulting in plagiarism and academic fraud. Originality, creativity, synthesis, and critical thinking, diligent editing are still necessary. AI technologies have theological ramifications for soteriology and ecclesiology. ChatGPT's biblical knowledge is theologically unsound and prone to errors. It’s unreliable in translations of ancient Biblical texts and should not replace professional knowledge of languages, particularly when handling intricate linguistic problems. Thus, AI technology should be viewed as a supportive tool for missions. It should not replace spiritual discernment, the Holy Spirit's guidance, theological understanding, or insights into the Christian experience.